PENGARUH PEMBERIAN PAKAN CACING SUTRA (TUBIFEX SP) DENGAN FREKUENSI YANG BERBEDA TERHADAP PERTUMBUHAN BENIH IKAN LELE SANGKURIANG (CLARIAS SP): Giving Effect of Silk Worms Feed (Tubifex Sp)With Different Frequency on The Growth of Seed Fish Sangkuriang Catfish (Clarias Sp) - Haerunnisa, Haerunnisa; Kurniawati, Kurniawati; Sumahiradewi, Luh Gede; Septian, I Gede Nano (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The aim of this research is to determine the most effective and efficient feeding frequency so that it can influence the growth of Sangkuriang catfish fry. This type of research is experimental research using analysis of variance (ANASRA). This research was carried out at the Batu Kumbung Fish Seed Center (BBI), Lingsar District, West Lombok Regency. The results of analysis of variance regarding the effect of feeding silk worms with different feeding frequencies on the growth of Sangkuriang catfish seeds showed very significantly different results where F count > F table 1% (26 > 8.02). Further test results using the least significant difference test (BNT) showed that there was a significant difference between P1 and P2 (0.072 > BNT 0.0715), significantly different between treatments P1 and P3 (0.161 < BNT 0.0715) and significantly different between P2 and P3 (0.089 > BNT 0.0715)